2002
DOI: 10.1002/jmri.10134
|View full text |Cite
|
Sign up to set email alerts
|

Axillary lymph node metastases: A statistical analysis of various parameters in MRI with USPIO

Abstract: Purpose:To assess the value of plain vs. iron oxide-enhanced MRI vs. the combined study (plain ϩ postcontrast) based on qualitative and quantitative parameters of three pulse sequences. Materials and Methods:Data from two sites were acquired using the same technique; therefore, this data could be pooled. T1W-SE, T2W-FSE, and 3D-PSIF were used before and 24 -36 hours after MRI with ultra small particles of iron oxide (USPIO) was performed. A total of 52 lymph nodes (LNs) in nine patients (25 benign, 27 malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…Due to the longer circulation time of dextran-coated USPIO as a result of the lower accumulation in the RES of the liver and spleen and the small size of USPIO compared to SSPIO, these can exit the vascular system after intravenous application (extravasation), are transported lymphogenically, and are absorbed physiologically in the lymph nodes by macrophages, resulting in a signal loss of the lymph nodes in T2w and in particular T2*w gradient echo sequences. Depending on the extent of the lymph node invasion, metastatic lymph nodes exhibit this signal loss only partially or not at all as could be shown in clinical studies in carcinomas of the head-neck [73], breast [74], bronchus [75], esophagus [76], stomach [77], rectum [78], and in pelvic/urological carcinomas [79], and can therefore result in an improvement of the lymph node staging. However, USPIO are currently not approved for clinical application.…”
Section: Lymph Node Imagingmentioning
confidence: 79%
“…Due to the longer circulation time of dextran-coated USPIO as a result of the lower accumulation in the RES of the liver and spleen and the small size of USPIO compared to SSPIO, these can exit the vascular system after intravenous application (extravasation), are transported lymphogenically, and are absorbed physiologically in the lymph nodes by macrophages, resulting in a signal loss of the lymph nodes in T2w and in particular T2*w gradient echo sequences. Depending on the extent of the lymph node invasion, metastatic lymph nodes exhibit this signal loss only partially or not at all as could be shown in clinical studies in carcinomas of the head-neck [73], breast [74], bronchus [75], esophagus [76], stomach [77], rectum [78], and in pelvic/urological carcinomas [79], and can therefore result in an improvement of the lymph node staging. However, USPIO are currently not approved for clinical application.…”
Section: Lymph Node Imagingmentioning
confidence: 79%
“…Its value awaits further evaluation in a large number of cases to conclude whether ADC value measurement of the nodes is helpful in differentiating metastatic from nonmetastatic nodes in breast cancer. USPIO, a lymphographic contrast medium of ironcontaining nanoparticles, has been shown to be useful in the characterization of lymph nodes in neck (7), esophageal (13), gastric (14), prostate (15), bladder (16), and breast cancers (17)(18)(19)(20). After IV injection of USPIO, the nanoparticles circulate systemically and access the interstitium.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to axillary lymph node staging, there are published data for USPIO-enhanced MRI (17)(18)(19)(20). Researchers in those studies reported a sensitivity of 73%-100% and a specificity of 92%-98% in the nodeby-node evaluation using USPIO.…”
Section: Discussionmentioning
confidence: 99%
“…146 Bassa 1996, 147 Beer 2008, 148 Bombardieri 1996, 149 Burcombe 2002, 150 Crowe 1994, 151 Danforth 2002, 152 Harisinghani 2006, 153 Harisinghani 2004, 154 Hoh 1993, 155 Kelemen 2002, 156 Luciani 2009, 157 Noh 1999, 158 Palmedo 1997, 159 Scheidhauer 1996, 160 Smyczek-Gargya 2004, 161 Sun 2008, 162 Tse 1992, 163 Vansant 1996, 164 184 Matsushima 2008, 185 Mavi 2006, 186 Mortellaro 2009, 187 Mussurakis 1997, 188 Nieweg 1993, 189 Rotaru 2004, 190 Schirrmeister 2001, 191 Schirrmeister 2000, 192 Song 2006, 193 Stets 2002, 194 Torrenga 2001, 195 Ueda 2008, 196 Yang 2007 197 24 No relevant data Bock 1998, 198 Chen 2007, 199 Dose-Schwarz 2008, 200 Enya 2000, 201 Koga 2007, 202 Nakayama 2004, 203 Romer 1997, 204 Tiutin 2001, 205 Zhao 2007 206 9 Non-English language Al-Yasi 2002, 207 Altinyollar 200...…”
Section: Chaptermentioning
confidence: 99%